2017
DOI: 10.3389/fnsys.2017.00055
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Fat Body Tyramine Level on Gustatory Responsiveness of Honeybees (Apis mellifera) Differ between Behavioral Castes

Abstract: Division of labor is a hallmark of social insects. In the honeybee (Apis mellifera) each sterile female worker performs a series of social tasks. The most drastic changes in behavior occur when a nurse bee, who takes care of the brood and the queen in the hive, transitions to foraging behavior. Foragers provision the colony with pollen, nectar or water. Nurse bees and foragers differ in numerous behaviors, including responsiveness to gustatory stimuli. Differences in gustatory responsiveness, in turn, might be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 38 publications
1
45
1
Order By: Relevance
“…Scouts have elevated amounts of tyramine in their brains compared to recruits (Figure c). These biogenic amines have been implicated in learning and foraging behaviour (Scheiner, Reim, Eirik, Entler, & Barron, ; Scheiner et al., ). Previous research found a QTL for learning differences using the same LI assay was linked to a specific area of the genome, Pln2 (or lrn1; 17).…”
Section: Discussionmentioning
confidence: 99%
“…Scouts have elevated amounts of tyramine in their brains compared to recruits (Figure c). These biogenic amines have been implicated in learning and foraging behaviour (Scheiner, Reim, Eirik, Entler, & Barron, ; Scheiner et al., ). Previous research found a QTL for learning differences using the same LI assay was linked to a specific area of the genome, Pln2 (or lrn1; 17).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to Vg, malvolio underwent duplication and subfunctionalization in multiple social and subsocial insects, which raises the question as to whether the role of malvolio in honey bees can be extended to other insects [63]. The neuromodulators tyramine and its precursor octopamine promote the onset of foraging, are involved into the rewarding system in honey bee foragers and increase gustatory responsiveness [28,64–66], but their role in other species is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…As age and fertility additionally influence gene expression [22,28,67,68], studies that did not experimentally control for age and physiology when comparing gene expression between brood carers and foragers [e.g. 28,31,46,56,57,6973] might have produced results driven not only by behaviour, but also by age and fertility. Such confounded transcriptomic analyses are not a problem specific to research on insect behaviour but occur across study systems and contexts.…”
Section: Introductionmentioning
confidence: 99%
“…S1). Like in earlier studies (Behrends et al, ; Thamm and Scheiner, ; Değirmenci et al, ; Scheiner et al , ; ). Foragers were more responsive to sucrose than nurse bees were, supporting the hypothesis that nutrition‐related pathways are possibly involved in the regulation of task allocation.…”
Section: Discussionmentioning
confidence: 99%
“…In the GG, about 40 motoneurons are involved in controlling the proboscis extension response (Rehder, 1989). In the mushroom bodies, several sensory modalities, including gustatory and mechanosensory information, converge (Schröter and Menzel, 2003). Experiments with blowflies suggest that these structures are involved in the feeding threshold determination (Nisimura et al, 2005).…”
Section: Division Of Labour Correlates With Amforα-pkg Level But Not mentioning
confidence: 99%